Gender Equality in Mosque Management: Women's Involvement in Masjid Raya Mujahidin Pontianak - Nurjamilah, Cucu (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
In the context of da’wah management, the functions of the mosque are not optimal yet. The activities of the masjid are only focused on the center of worship, religious activities, but have not touched the equality yet. In order to answer the problems above, the researcher used fieldwork with the method of case studies. Through an in-depth interview technique, participant observation and study of documentation found that Masjid Mujahidin Pontianak has involved women in the management of masjid, and succeeded in increasing the functions of a mosque. Involving women in the management of mosque will strengthen one dimension that is important in Islam that is Islam seriously upholds the equality of degree in various aspect, including Islam is a religion that highly responsive gender. When the management of mosque is filled with a variety of different groups, including giving places to women, then frictions and clashes caused by differences in the understanding in the society will be minimized, and then the role and function of masjid will be able to touch various aspects such as economics, health, and education. Dalam konteks pengelolaan dakwah, fungsi masjid sebagai media dakwah belum diberdayakan secara optimal. Kegiatan masjid yang ada hanya digunakan sebagai pusat ibadah dan aktivitas keagamaan, selebihnya belum menyentuh pada persoalan gender. Guna menjawab permasalahan di atas, dilakukan studi lapangan dengan metode studi kasus. Melalui teknik wawancara mendalam, observasi partisipan dan dokumentasi, ditemukan bahwa Masjid Raya Mujahidin Pontianak telah melibatkan perempuan dalam kepengurusan masjidnya, dan berhasil dalam peningkatan fungsi masjid. Melibatkan perempuan dalam pengelolaan masjid, akan menguatkan satu dimensi penting dalam Islam yaitu Islam menjunjung tinggi persamaan derajat dalam berbagai segi, termasuk Islam adalah agama yang responsif gender. Ketika kepengurusan masjid diisi dari berbagai golongan, termasuk mengapresiasi kaum perempuan, maka gesekan-gesekan yang disebabkan perbedaan pemahaman di masyarakat akan dapat diminimalisir, serta fungsi dan peran masjid akan mampu menyentuh berbagai aspek seperti bidang ekonomi, kesehatan, dan pendidikan.